Odpowiedzi

2009-10-11T09:04:37+02:00
B) (6x+12- x²-2x)+(x²-4x+3x-12)=2x+5
6x+12-x²-2x+x²-4x+3x-12=2x+5
3x≠2x+5
g) (x-5)(x+2)-(3-x)(2-x)=x - 12
(x²+2x-5x-10)-(6-3x-2x+x²)=x-12
x²+2x-5x-10-6+3x+2x-x²+x-12
2x-16≠x-12
r) (2x-5)(x+1)-2=(1-x)(8-2x)+2x
(2x²+2x-5x-5)-2=(1-2x-8x+2x²)+2x
2x²-3x-7≠1-8x+2x²
5.b)x²-9+10=x²-4x+4+x
c)4x²+12x+9+1=4(x²-4)-5x-8
4x²+12x+10=4x²-16-5x-8
4x²+12x+10=4x²- 24-5x
Najlepsza Odpowiedź!
  • Użytkownik Zadane
2009-10-11T09:35:22+02:00
B)
(6-x)(x+2)+(x+3)(x-4)=2x +5
(6x+12-x²-2x)+(x²-4x+3x-12)=2x+5
4x+12-x²+x²-x-12-2x=5
x=5

g)
(x-5)(x+2)-(3-x)(2-x)=x - 12
(x²+2x-5x-10)-(6-3x-2x+x²)=x-12
x²-3x-10-6+5x-x²-x=-12
x=-12+16
x=4

r)
(2x-5)(x+1)-2=(1-x)(8-2x)+2x
(2x²+2x-5x-5)-2=(8-2x-8x+2x²)+2x
2x²-3x-5-2=8-10x+2x²+2x
2x²-2x²-3x+8x=8+7
5x=15 [/:5]
x=3

5.
b)
(x-3)(x+3)+10= (x-2)²+x
x²-9+10=x²-4x+4+x
x²-x²+3x=4-1
3x=3 [/:3]
x=1

c)
(2x+3)²+1 = 4(x-2)(x+2) - 5x-8
4x²+12x+9+1=4x²-16-5x-8
4x²-4x²+12x+5x=-24-10
17x=-34 [/:17]
x=-2

:)
2009-10-11T11:06:04+02:00
B) (6-x)(x+2)+(x+3)(x-4)=2x +5
6x+12-x²-2x+x²-4x+3x-12=2x+5
6x-x²-2x+x²-4x+3x-2x=5-12+12
x=5
g) (x-5)(x+2)-(3-x)(2-x)=x - 12
x²+2x-5x-10-(6-3x-2x+x²)=x-12
x²+x-5x-10-6+3x+2x-x²=x-12
x²+x-5x+3x+2x-x²-x=-12+10+6
x=4
r)(2x-5)(x+1)-2=(1-x)(8-2x)+2x
2x²+2x-5x-5-2=8-2x-8x+2x²+2x
2x²+2x-5x+2x+8x-2x²-2x=8+5+2
5x=15/ :5
x=3
5. do tego trzeba uzyc wzory skróconego mnozenia
b)(x-3)(x+3)+10= (x-2) do kwadratu +x
x²-9+10=x²-4x+4+x
x²-x²+4x-x=4+9-10
3x=3 /:3
x=1
c) (2x+3) do kwadratu +1 = 4(x-2)(x+2) - 5x-8
4x²+12x+9+1=4x²-16
²4x+12x-4x²=-16-9-1
12x=-26